2023
DOI: 10.3389/fcvm.2023.1138787
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 inhibitors for acute coronary syndrome: the era of early implementation

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, a new cholesterol-lowering strategy, can decrease low-density lipoprotein cholesterol (LDL-C) levels by inhibiting PCSK9 and reducing the degradation of LDL receptors; thus, they are impacting the management of dyslipidemia to the prevention of cardiovascular events. Recent guidelines recommend PCSK9 inhibitors for patients who fail to achieve target lipids after ezetimibe/statin therapy. As PCSK9 inhibitors have been demonstrated to significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…It was shown that the use of HIS with evolocumab, compared to HIS monotherapy, led to a reduction in serum LDL-C concentration after 8 weeks by 40.7%, which was related to the fact that 95.7% of patients were in at the therapeutic target (vs. 37.6% in HIS monotherapy) [ 42 ]. Recent evidence also demonstrated the benefits of early PCSK9 inhibitors in lipid reduction, plaque stabilization, and short-term or long-term cardiovascular event prevention [ 43 ].…”
Section: Upfront Lipid Lowering Combination Therapy Of High Intensity...mentioning
confidence: 99%
“…It was shown that the use of HIS with evolocumab, compared to HIS monotherapy, led to a reduction in serum LDL-C concentration after 8 weeks by 40.7%, which was related to the fact that 95.7% of patients were in at the therapeutic target (vs. 37.6% in HIS monotherapy) [ 42 ]. Recent evidence also demonstrated the benefits of early PCSK9 inhibitors in lipid reduction, plaque stabilization, and short-term or long-term cardiovascular event prevention [ 43 ].…”
Section: Upfront Lipid Lowering Combination Therapy Of High Intensity...mentioning
confidence: 99%
“…These pleiotropic effects of PCSK9 inhibitors have also observed in small human studies ( 11 , 13 ), with follow-up studies using IVUS showing regression of atherosclerotic plaques ( 14 ). Based on these insights, several recent and ongoing studies have been employing PCSK9 inhibitors early in the treatment process and off-label for patients with acute myocardial infarction who are receiving percutaneous coronary intervention ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%